Identificação e caracterização da expressão gênica das proteínas Rad23 e Rad4, da via de reparo por excisão de nucleotídeos, durante o ciclo evolutivo de Schistosoma mansoni - Silva, Camila Siqueira (2006)
DNA is often damaged by environmental agents which lead to the up-regulation of several genes involved in different repair pathways. The regulation of DNA repair is important for cell survival following exposure to DNA-damaging agents. Schistosoma mansoni is a parasite that undergoes several modifications in its complex life cycle, being exposed to a subset of DNA-damaging agents, such as the environment and host immune response, and therefore, such as many other organisms, it is likely to be provided for efficient repair mechanisms. Recently, studies have shown that Nucleotide Excision Repair (NER) consists in an indispensable mechanism for removing a broad spectrum of DNA lesions. In the current study, it was analyzed the gene expression of Nucleotide Excision Repair Factor 2 (NEF2) - SmRad23 and SmRad4, in different developmental stages of S. mansoni, as well as the expression level of these genes in S. mansoni adult worms treated with DNA-damaging agents. Together, the results have confirmed the expression of these two proteins in all of the evolutive stages studied of the parasite, and shown a differential expression in front of the treatment with the different chemical agents. Furthermore, it was revealed the correlation of these genes with their orthologues in other eukaryotes. Therefore, the presence of SmRad23 and SmRad4 in all of the developmental stages of S. mansoni, as well as their differential expression following exposition to DNA-damaging agents, suggest that the NER is an important repair pathway during the complex life cycle of this parasite.